1724. Characteristics of the Ongoing Measles Outbreak in Greece in the Context of the Recent European-wide Epidemic and Public Health Measures. (26th November 2018) - Georgakopoulou, Theano; Horefti, Elina; Maltezou, Helena; Gkolfinopoulou, Kassiani; Vernardaki, Alexandra; Triantafyllou, Eleni; Mavraganis, Pantelis; Pogka, Vasiliki; Theodoridou, Maria; Panagiotopoulos, Takis; Mentis, Andreas; Tsiodras, Sotirios
Abstract: Background: Measles is a highly contagious disease which still remains a cause of severe complications, including deaths worldwide, despite the existence of safe and effective vaccines. In the last 3 decades, the incidence of measles in Greece has constantly declined with only sporadic clusters or outbreaks (last outbreak in 2010–2011). We describe the characteristics of the ongoing measles outbreak and the Public Health response. Methods: All measles cases are reported through the mandatory notification system (EU case definition 2012) to the Department of Surveillance and Intervention of the Hellenic Centre for Disease Control and Prevention. For laboratory confirmation patient sera were tested for IgM antibodies and pharyngeal swabs for the presence of measles virus RNA with RT-PCR. Sequencing of the measles nucleoprotein gene was applied in positively tested serological samples. Results: From 9 May 2017 to 26 April 2018, 2, 659 cases were reported in all 13 regions in Greece; 1, 605 (60.4%) were laboratory confirmed. Most cases ( n = 1, 595; 60%) were Roma (73% children <10 years) followed by nonminority Greek nationals ( n = 781; 29.4%, of whom 57% young adults 25–44 years), highlighting the immunity gap in Roma population. The vast majority of cases (80.5%) were unvaccinated. Ninety-four (3.5%) cases were healthcare workers (HCW); all were partially or not vaccinated. Genotype B3 was identified by molecular testing in all 88 cases tested. Severe complications were reported in 429 (16.1%) patients, most frequently pneumonia (43.8%) and hepatitis (21.2%). Three deaths were recorded in an 11-month-old immunocompromised Roma infant, a 17-year-old unvaccinated Roma, and a 35 year olds partially vaccinated individual from the general population. Extensive vaccination in refugee/migrant hosting sites prevented the emergence of a large number of cases. Mitigation efforts focused on closing the immunization gap in Roma population through emergency vaccination and raising awareness among HCWs to prevent further spread. Conclusion: The current outbreak highlights the need to achieve high vaccination coverage with 2 doses of MMR vaccine in the general population (children, adolescents, and young adults) and in hard-to-reach vulnerable populations like Roma and refugees. Disclosures: All authors: No reported disclosures.